Mastitis Pain in Postpartum Mothers Using Plumeria Rubra L Ointment - Zakaria, Rabia; Astuti, Siti Choirul Dwi; Agustini, Rahma Dewi; Damiti, Sukmawati A.; Mashar, Harlyanti Muthmai’nnah (Jurnal Kesehatan Masyarakat, 2024)
Treatment of mastitis is usually carried out pharmacologically by giving antibiotics, but the content of antibiotics can enter breast milk, so an alternative solution is needed for the problem of using herbal plants. Plumeria rubra L is processed into an ointment so that it is easy to use. The aim of this study was to determine the intensity of postoartum maternal mastitis pain in the use of 5% Plumeria rubra L ointment. The research design is true experiment pre post test control group design. Respondents were divided into 2 groups, namely intervention and control totaling 32 people. The intervention was given by 5% Plumeria rubra L ointment applied to the breasts of postpartum mothers who were given twice a day in the morning and evening for seven days with a size of 5 grams for each using. The result is the intensity of postpartum mastitis pain in the previous control group, most of the percentage was severe pain as much as 66.7% and after most of the presentations, namely moderate pain as much as 60.0%. The intensity of mastitis pain for postpartum mothers before using red frangipani ointment is mostly the percentage, namely severe pain 73.3% and the intensity of mastitis pain for postpartum mothers after using red frangipani ointment, most of the percentages are moderate pain 53.3%. The conclusion obtained is a p value of 0.004 which indicates a significant difference. To reduce mastitis pain, postpartum mothers can use red frangipani ointment for 7 days.